PENGEMBANGAN LKPD BERMUATAN STRATEGI “IDEAL” DALAM MATERI PROGRAM LINEAR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Stepanus Daling; Edi Tandililing; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis research is a development research that refers to a 4D (four-D) development model that has been modified into 3D which includes three stages, namely: the definition stage, the design stage and the develop stage. The instrument used in this research is a questionnaire. The results of LKPD development are known that: (1) Based on the results of descriptive data analysis explaining that teachers and students need the development of LKPD containing the "IDEAL" strategy in Linear Program material (2) The level of LKPD validity based on the results of material and media expert validation is (96.88 %) is in the very valid category and (3) the level of practicality of the LKPD based on the results of teacher assessments and student responses (92.02%) is included in the very practical category.Keywords: LKPD, Mathematical Problem Solving Ability, “IDEAL” strategy, Program Linear